Assessment of preoperative risk scoring systems in geriatric and non-geriatric coronary bypass surgery patients - Kartal, Hakan; Sicim, Hüseyin; Mungan, Ufuk; Demirdaş, Ertan; Erol, Gökhan; Ocal, Arslan; Koç, Murat (Journal of Surgery and Medicine, 2020)
Aim: The need to predict mortality in patients undergoing cardiac surgery has resulted in the development of numerous preoperative risk scoring systems, which are being successfully implemented in clinical practice. Although the criteria of scoring systems use patient age as a risk factor, their effectiveness should also be evaluated in the subgroups of these systems. Methods: Our retrospective cohort study includes all patients who underwent isolated CABG surgery at Private Akay Hospital Cardiovascular Surgery Clinic between May 2012 and March 2014. Patients were subdivided into two cohorts as geriatric (≥65 years) and non-geriatric (<65 years) patients. In this study, intraoperative deaths and deaths within 30 days postoperatively were considered as mortality. We retrospectively evaluated demographic data, preoperative risk factors, preoperative treatments, postoperative data, postoperative complications, laboratory findings, and mortality and morbidity outcomes from patient files and the hospital database. Results: The coherence between observed and EuroSCORE II-predicted mortality, logistic Euro-SCORE-predicted mortality and Parsonnet-predicted mortality were 93%, 94%, and 89%, respectively for patients aged 65 and older, and 78%, 77%, and 71%, respectively for patients aged below 65 years (P=0.01 for all). Conclusion: In general, we observed that EuroSCORE II, Log EuroSCORE and Log Parsonnet scoring systems are more effective in predicting mortality among elderly coronary bypass surgery patients compared to younger patients.